Analysis of failure modes and solutions in the process of post open-heart surgery using Fuzzy FMEA and Fuzzy TOPSIS Techniques - shima Tasharoei; Ali Jahan; kamran Ghods (Tehran University of Medical Sciences, 2019)
Introduction: Intensive Care Unit (ICU) in hospitals is one of the most sensitive and costly units which is really important due to safety and health of patients during their stay in these units. Hence, considering the potential risks in this unit, treatment operations for eliminating or decreasing risks are very important. Among these intensive care units, the most important one is the open-heart surgery unit which may have irreparable damages due to vulnerability of these patients in the process of their transfer, care, and discharge. The present study aims to identify the potential risks and offer solutions for eliminating or decreasing them. Method: In this research, we used Failure Mode and Effect Analysis (FMEA) method, which is a very useful method for evaluating and managing the risks, to prioritize risk factors. Due to some limitations of the method, fuzzy FMEA and fuzzy TOPSIS methods were also used in order to have more precise results and then the results were compared with each other. Results: The suggested approach was implemented in ICU-OH (open-heart) unit of Kowsar hospital in Semnan. Finally, nineteen factors were recognized as major risk factors. Also, corrective actions were determined for all detected risks that can be pursued according to their priorities. Conclusions: Factors including not observing hemodynamic signs, not considering patient safety and security, and inability to interpret arterial gas valve abnormalities are the three top risk factors that can be addressed through training and having more control on nurses.